The bouncer [videorecording (DVD)] - Milnes, Adrian; Ozuna, John; Mandylor, Costas, 1965-; Yaneva, Rosemary; Turturro, Nicholas (Vision Films, 2024)
An expat on the run works as a bouncer at an upscale nightclub frequented by a notorious mob boss and his girlfriend. When he saves the woman from being abused, the two go on the run as the vengeful boss and his army of henchmen relentlessly pursue them. With nobody to trust and merciless killers closing in, they'll have to use their fists, guns, and wits if they want to survive.